A survey of simian Plasmodium infections in humans in West Kalimantan, Indonesia - Sri Riyati, Sugiarto; Diana, Natalia; Dayang Shuaisah Awang, Mohamad; Nawal, Rosli; Wendy A., Davis; J. Kevin, Baird; Balbir, Singh; Iqbal, Elyazar; Paul Cliff Simon, Divis; Timothy M.E., Davis (Springer Nature, 2022)
The simian parasite Plasmodium knowlesi is the predominant species causing human malaria infection, including hospitalisations for severe disease and death, in Malaysian Borneo. By contrast, there have been only a few case reports of knowlesi malaria from Indonesian Borneo. This situation seems paradoxical since both regions share the same natural macaque hosts and Anopheles mosquito vectors, and therefore have a similar epidemiologically estimated risk of infection. To determine whether there is a true cross-border disparity in P. knowlesi prevalence, we conducted a community-based malaria screening study using PCR in Kapuas Hulu District, West Kalimantan. Blood samples were taken between April and September 2019 from 1000 people aged 6 months to 85 years attending health care facilities at 27 study sites within or close to jungle areas. There were 16 Plasmodium positive samples by PCR, five human malarias (two Plasmodium vivax, two Plasmodium ovale and one Plasmodium malariae) and 11 in which no species could be definitively identified. These data suggest that, if present, simian malarias including P. knowlesi are rare in the Kapuas Hulu District of West Kalimantan, Indonesian Borneo compared to geographically adjacent areas of Malaysian Borneo. The reason for this discrepancy, if confirmed in other epidemiologically similar regions of Indonesian Borneo, warrants further studies targeting possible cross-border differences in human activities in forested areas, together with more detailed surveys to complement the limited data relating to monkey hosts and Anopheles mosquito vectors in Indonesian Borneo.